Perception of Personality Traits in Crowds of Virtual Humans - Nardino, Lucas; Schaffer, Diogo; Elsner, Felipe; Krzmienszki, Enzo; Araujo, Victor Flávio de Andrade; Silva, Gabriel Fonseca; Cassol, Vinícius Jurinic; Favaretto, Rodolfo Migon; Musse, Soraia Raupp (Proceedings of the Brazilian Symposium on Computer Games and Digital Entertainment (SBGames), 2021)
This paper proposes a perceptual visual analysis regarding the personality of virtual humans. Many studies have presented findings regarding the way human beings perceive virtual humans with respect to their faces, body animation, motion in the virtual environment and etc. We are interested in investigating the way people perceive visual manifestations of virtual humans’ personality traits when they are interactive and organized in groups. Many applications in games and movies can benefit from the findings regarding the perceptual analysis with the main goal to provide more realistic characters and improve the users’ experience. We provide experiments with subjects and obtained results indicate that, although is very subtle, people perceive more the extraversion (the personality trait that we measured), into the crowds of virtual humans, when interacting with virtual humans behaviors, than when just observing as a spectator camera.